Fire Alarm Smart System Technology (FASTech) - Sharifah Saon; Amirrul Atiman; Abd Kadir Mahamad (Vol. 1 No. 1 (2019): Internet of Things: Tracking & Monitoring, 2022)
Fire alarm system is the most essential elements of building’s safety systems. This is one of the protection systems that can be used to safe human life from the fire strikes in the building whether at home, warehouse, office or etc. Not only to save lives when fire strikes happen but, it is often regulate other systems in the building and able to save huge amounts of money by reducing damage to the building structures and the appliances. Besides that, fire alarm system also contribute in reducing environmental damage cause from fire accident. The first action toward halting a fire is identifying the incident properly, raise the occupant alarm and then notify the incident to professional’s emergency response. This is often functioning of fire alarm system and fire detection. Several system types and option are available depend on the specific characteristics of the protected space.